A review of renewable off-grid mini-grids in Sub-Saharan Africa - Babayomi, Oluleke O.; Olubayo, Babatunde; Denwigwe, Iheanacho H.; Somefun, Tobiloba E.; Adedoja, Oluwaseye Samson; Somefun, Comfort T.; Olukayode, Kevwe; Attah, Amarachi (Frontiers in Energy Research, 2023)
Sub-Saharan Africa (SSA) is home to 75% of the world’s unelectrified population, and approximately 500 million of these live in rural areas. Off-grid mini-grids are being deployed on a large scale to address the region’s electrification inequalities. This study aims to provide a comprehensive review of the research on the off-grid renewable mini-grids in SSA. The study covers the current status of the level of deployment of off-grid mini-grids. It also reviews multi-criteria decision-making models for optimizing engineering, economics, and management interests in mini-grid siting and design in SSA. The statuses of financing, policy, and tariffs for mini-grids in SSA are also studied. Finally, the current status of energy justice research in respect of mini-grids in SSA is reviewed. The study shows the important role of decentralized renewable technologies in the electrification of SSA’s rural population. Within a decade since 2010, the rural electrification rate of SSA has increased from 17% to 28%, and 11 million mini-grid connections are currently operational. Despite these gains, the literature points to several injustices related to the present model by which SSA’s renewable mini-grids are funded, deployed, and operated. Hence, several recommendations are provided for the effective application of the energy justice framework (EJF) for just and equitable mini-grids in SSA.